Iodisasi Garam - Djumarman Djumarman (Jurnal Kimia dan Kemasan, 1978)
Iodization of salt is processe in which iodine in the form of potassium Iodate solution, is added. into salt , The materials needed for the purpose are : salt (NaCl), potassium iodate (KIO3) and water. Iodized salt in Indonesia should contain 40 ppm of potassium Iodate,with 10 ppm tolerable deviation.